Improved life cycle performance of mechanical ventilation systems. (TM (Chartered Institution of Building Services Engineers), 2003)
Introduces designers to the performance standards for air conditioning and mechanical ventilation systems originating from Part L (2002). It will benefit anyone who wants to obtain a reliable prediction of costs of ownership of a ventilation system. It will be highly relevant to PFI bidders and to owners of systems.